High-temperature compressive behavior and kinetics analysis of Al0.4MnCrCoFeNi high entropy alloy - Hamed Kaypour; Said Nategh; Reza Gholamipour; Alireza Khodabandeh (Materials Research Express, 2021)
In the present study, Al _x MnCrCoFeNi alloys (x = 0, 0.4) were produced by vacuum melting and casting. For this aim, ingots were subjected to the homogenization, cold roll, and annealing. X-ray diffraction analysis and SEM images indicated that the crystal structure is FCC solid solution for MnCrCoFeNi. Moreover, in addition to FCC solid solution, the alloy with aluminum (x = 0.4) ordered B2 precipitates. Besides, hot compressive tests were conducted at different temperatures and strain rates of 0.01, 0.05 and 0.1/s. Investigating the stress-strain diagrams and work hardening rate, it was revealed that twins played a role in the deformation mechanism. In the constitutive equation, the values of the stress exponent and activation energy were measured and they were 6.86 and 434 kJ mol ^−1 , respectively. The exponential equations of peak stress and peak strain, as well as steady-state stress, were obtained due to the Zener-Hollomon parameter. Regarding the linear relationship between the work hardening rate and the dislocation annihilation coefficients, the activation energy of deformation changes at 600 °C. Finally, another effect of the Al addition was shown to be increase in initiation temperature of necklace structure about 200 °C in hot compression test. In addition, B2 nanoprecipitate and nanotwins indicated that there was twin deformation mechanism in alloy containing Al.